163Ho based experiments - Gastaldo, Loredana (XXVI International Conference on Neutrino Physics and Astrophysics, 2015)
The analysis of the endpoint region of the calorimetrically measured 163Ho electron capture spectrum is a very promising way to determine the mass of the electron neutrino. The achievable sensitivity of 163Ho-based experiments and the experimental challenges will be presented. Three large collaborations aim at developing large scale experiments able to reach sub-eV sensitivity. Presently pilot experiments are performed to demonstrate the possibility to calorimetrically measure high precision and high statistics 163Ho spectra. The different approaches as well as the state of the art of the experimental efforts for the three collaborations will be discussed.